2017
DOI: 10.1128/aem.01519-17
|View full text |Cite
|
Sign up to set email alerts
|

Lactolisterin BU, a Novel Class II Broad-Spectrum Bacteriocin from Lactococcus lactis subsp. lactis bv. diacetylactis BGBU1-4

Abstract: subsp. bv. diacetylactis BGBU1-4 produces a novel bacteriocin, lactolisterin BU, with strong antimicrobial activity against many species of Gram-positive bacteria, including important food spoilage and foodborne pathogens, such as, , spp., and streptococci. Lactolisterin BU was extracted from the cell surface of BGBU1-4 by 2-propanol and purified to homogeneity by C solid-phase extraction and reversed-phase high-performance liquid chromatography. The molecular mass of the purified lactolisterin BU was 5,160.94… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Additionally, the structure genes and the genes encoding the putative biosynthetic enzymes of weissellicin Y and M and enterocin MR10 (MR10A and B) seem to be encoded in the chromosomal DNA of its producer strains Weissella hellenica QU 13 ( Masuda et al, 2012a ) and Enterococcus faecalis MRR10-3 ( Martín-Platero et al, 2006 ), respectively. Whereas the plasmid-encoded genetic determinants for the leaderless bacteriocins enterocin EJ97 ( Sánchez-Hidalgo et al, 2003 ), lactolisterin BU ( Lozo et al, 2017 ), garvicin KS ( Ovchinnikov et al, 2016 ), cereucin H, V, and X ( Ovchinnikov et al, 2016 ), and epidermicin NI01 ( Sandiford and Upton, 2012 ) have also been described. Although, the specific functions of the gene products encoded in these putative biosynthetic genes have remained unconfirmed.…”
Section: Leaderless Bacteriocinsmentioning
confidence: 99%
“…Additionally, the structure genes and the genes encoding the putative biosynthetic enzymes of weissellicin Y and M and enterocin MR10 (MR10A and B) seem to be encoded in the chromosomal DNA of its producer strains Weissella hellenica QU 13 ( Masuda et al, 2012a ) and Enterococcus faecalis MRR10-3 ( Martín-Platero et al, 2006 ), respectively. Whereas the plasmid-encoded genetic determinants for the leaderless bacteriocins enterocin EJ97 ( Sánchez-Hidalgo et al, 2003 ), lactolisterin BU ( Lozo et al, 2017 ), garvicin KS ( Ovchinnikov et al, 2016 ), cereucin H, V, and X ( Ovchinnikov et al, 2016 ), and epidermicin NI01 ( Sandiford and Upton, 2012 ) have also been described. Although, the specific functions of the gene products encoded in these putative biosynthetic genes have remained unconfirmed.…”
Section: Leaderless Bacteriocinsmentioning
confidence: 99%
“…In a previous study, it was reported that Lactococcus lactis subsp. lactis BGBU1-4 contains a plasmid, pBU6, carrying the structural lactolisterin BU operon ( Lozo et al, 2017 ). Based on comparisons with known bacteriocin clusters, it was hypothesized that the lactolisterin BU bacteriocin operon was organized into a four gene operon-like structure consisting of ( lliBU ) the structural gene; ( abcT ) an ABC transporter; and hyp1 and hyp2 genes to which the exact function has not been attributed.…”
Section: Resultsmentioning
confidence: 99%
“…and streptococci. The production of lactolisterin BU is related to the smallest plasmid pBU6 of 6.2 kb, which contains nine open reading frames (ORFs): repB , lliBU , abcT , hyp1 , hyp2 , hyp3 , mobC , relM , and rnaY ( Lozo et al, 2017 ). An identity (BLAST) search within the lactolisterin BU operon recognized the product of the abcT gene as a sugar transporter, while other genes were designated as hypothetical.…”
Section: Introductionmentioning
confidence: 99%
“…A key emerging group of antimicrobial peptides include the bacteriocins which are produced by Lactic Acid Bacteria (LAB). Bacteriocins are ribosomally synthesized hydrophobic peptides which usually display activity towards bacteria closely related to the producer (Lozo et al 2017) and may be subdivided based on whether or not they have undergone post translational modifications (Class I) or not (Class II). This group of antimicrobial peptides exhibit enhanced potency, are biocompatible and stable and can have a narrow or broad range spectrum of activity .…”
Section: Introductionmentioning
confidence: 99%
“…This bacteriocin has a very narrow spectrum of activity and could be used specifically to treat C. difficile infections of the gut. (Acedo et al 2017, Ahn et al 2017, Lozo et al 2017. Enterocin NKR-5-3, a class IIa bacteriocin, shows potent activity against Listeria spp.…”
Section: Introductionmentioning
confidence: 99%